ANALYSIS OF HUMAN RESOURCE MANAGEMENT ON THE QUALITY OF HOSPITAL SERVIES - Mulia Sosiady; Ermansyah (Adisam Publisher, 2024)
Human resource management is an important part. The human resources that hospitals must have are in principle regulated through hospital accreditation. Efforts to improve the quality of human resources and the quality of service on public trust in public services must be made. The public questions the quality and effectiveness of public services. The quality of service in a hospital is a reflection of all the systems that are running within it. Apart from that, service quality is also the conformity of health services with professional standards by making good use of existing resources, so that all customer needs and goals for achieving optimal levels of health can be achieved. The human resources that hospitals must have are in principle regulated through Hospital accreditation is in determining the number and specifications of personnel and service supporting facilities that a hospital must have. Education and training are efforts to develop human resources, especially to develop intellectual abilities and personality. Education is generally related to preparing prospective workers for use by an organization, while training is more related to improving the abilities or skills of workers who already occupy a certain position or task.